2019
DOI: 10.1016/j.medin.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Safety of aerosol therapy in children during noninvasive ventilation with helmet and total face mask

Abstract: The probability of suffering an adverse effect related to nebulization is extremely low when using a helmet or TFM. Inhaled therapy with TFM may shorten PICU stay in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Moreover, H-CPAP seems to reduce cerebral blood flow more than nasal masks [ 98 ]. Some authors have suggested that helmets allow effective delivery of nitric oxide [ 99 ] or aerosols [ 100 ].…”
Section: Use In the Paediatric Populationmentioning
confidence: 99%
“…Moreover, H-CPAP seems to reduce cerebral blood flow more than nasal masks [ 98 ]. Some authors have suggested that helmets allow effective delivery of nitric oxide [ 99 ] or aerosols [ 100 ].…”
Section: Use In the Paediatric Populationmentioning
confidence: 99%
“…After titles and abstracts screening, 30 citations with full-text were retrieved for detailed evaluation. After reviewing, 18 studies were excluded for the following reasons: non-RCT (n = 6) [18][19][20][21][22][23], review article (n = 5) [24][25][26][27][28], subjects were infants (n = 3) [29][30][31], subjects were healthy volunteers (n = 2) [32,33], animal trial (n = 1) [34] and news (n = 1) [35]. Finally, seven English studies [9][10][11][12][36][37][38] and five Chinese studies [39][40][41][42][43] matched the inclusion criteria and were suitable for our meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%